Recent Progress in Proximity Coupling of Magnetism to Topological Insulators (Adv. Mater. 33/2021). Issue 33 (17th August 2021) - Bhattacharyya, Semonti; Akhgar, Golrokh; Gebert, Matthew; Karel, Julie; Edmonds, Mark T.; Fuhrer, Michael S.
Abstract : Functional Topological Materials Proximity coupling of topological insulators to magnets is a promising strategy to design functional topological materials with new properties including dissipationless conducting edge states and a strong magnetoelectric effect, useful for low‐power electronics. In article number 2007795, Semonti Bhattacharyya, Michael Fuhrer, and co‐workers review the latest progress in this field and provide an outlook on remaining challenges and opportunities.